(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The issue of feudalism in India started as a critique ofMarx’s concept of Asiatic Mode of Production. Marx rejected the categorizationof Indian property relations as feudal .Instead he advised the analysis ofpre-colonial India within the framework of Oriental Despotism and Asiatic Modeof production. Both Marx and Engels did not formulate the paradigm of AMP, butwe scattered references to these in their writings what runs through the ideaof oriental despotism and AMP in the state ownership of land.